Short period ScP phase amplitude calculations for core–mantle boundary with intermediate scale topography - Shen, Zhichao; Ni, Sidao; Wu, Wenbo; Sun, Daoyuan (Physics of the earth and planetary interiors, 2016)
•We developed a ray-based method for computing ScP waveforms with CMB topography.•A bump and dip relief on CMB would cause defocusing and focusing effects on ScP.•Effects of topography and frequency on ScP waveforms are quantified.•A CMB topography model beneath Japan could overall predict the observed data. The core–mantle boundary (CMB) topography plays a key role in constraining geodynamic modeling and core–mantle coupling. It’s effective to resolve the intermediate lateral scale topography (hundreds of km) with short period core reflected seismic phases (ScP) due to their small Fresnel-zones at short epicentral distances (<3336km (30°)). We developed a method based on the ray theory and representation theorem to calculate short period ScP synthetics for intermediate lateral scale CMB topography. The CMB topography we introduced here is axisymmetric and specified with two parameters: H (height) and L (diameter, or lateral length scale). Our numerical computation shows that a bump (H>0) and dip (H<0) model would cause defocusing/weakening and focusing/amplifying effects on ScP amplitude. Moreover, the effect of frequency and combination of L and H are quantified with the amplification coefficients. Then we applied this method to estimate a possible CMB topography beneath northeastern Japan, and a CMB model with L=140km, H=1.2km overall matches the observed pattern of 2D PcP/ScP amplitude ratios. However, it is difficult to totally rule out other factors that may also affect PcP/ScP pattern because of limitation of ray-based algorithms we used here. A hybrid method combining ray theory and numerical method is promising for studying complicated 3D structure and CMB topography in the future.